Comparison of the nucleotide sequence of cloned human and guinea-pig pre-alpha-lactalbumin cDNA with that of chick pre-lysozyme cDNA suggests evolution from a common ancestral gene. - Hall, L (1982)
Nucleotide sequence analyses of essentially full-length copies of human and guinea-pig pre-alpha-lactalbumin cDNAs contained within recombinant plasmids, (i) confirm the presence of 19 amino acid hydrophobic amino terminal peptide extensions encoded within each mRNA; and (ii) provides evidence for the existence of a minor variant of guinea-pig alpha-lactalbumin mRNA encoding a protein with a 36 residue carboxyl-terminal extension. Comparison of the nucleotide sequence within the coding region of the human, and the predominant guinea-pig pre-alpha-lactalbumin mRNAs, with the analogous region of hen pre-lysozyme mRNA provides compelling evidence that all have evolved from a common ancestral gene.